Conservation laws for Z(N) symmetric quantum spin models and their exact ground state energies - Alcaraz, Francisco C.; Lima Santos, A. [UNESP] (Elsevier B.V., 1986)
We derive an infinite set of conserved charges for some Z(N) symmetric quantum spin models by constructing their Lax pairs. These models correspond to the Potts model, Ashkin-Teller model and the particular set of self-dual Z(N) models solved by Fateev and Zamolodchikov [6]. The exact ground state energy for this last family of hamiltonians is also presented. © 1986.